2017
DOI: 10.1371/journal.pone.0186195
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistant Enterobacteriaceae colonization (CRE) and subsequent risk of infection and 90-day mortality in critically ill patients, an observational study

Abstract: BackgroundCarbapenem-resistant Enterobacteriaceae (CRE) have emerged as an urgent public health threat. Intestinal colonization with CRE has been identified as a risk factor for the development of systemic CRE infection, but has not been compared to colonization with third and/or fourth generation cephalosporin-resistant (Ceph-R) Enterobacteriaceae. Moreover, the risk conferred by colonization on adverse outcomes is less clear, particularly in critically ill patients admitted to the intensive care unit (ICU).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
146
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(164 citation statements)
references
References 29 publications
11
146
2
5
Order By: Relevance
“…Similar studies from other regions have reported VRE carriage rates ranging from 2 to 37% (13-15), while prevalence rates for CRGN rectal carriage ranged from 5.3 to 52% (16)(17)(18). At the same time, there is an increased risk of carbapenem-resistant enterobacteriaceae (CRE) infection and mortality in patients who test positive for carriage of CRE (19,20). To the best of our knowledge, there is no previous study from Greece focusing on both VRE and CRGN rectal carriage, exploring respective risk factors and adverse outcomes.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Similar studies from other regions have reported VRE carriage rates ranging from 2 to 37% (13-15), while prevalence rates for CRGN rectal carriage ranged from 5.3 to 52% (16)(17)(18). At the same time, there is an increased risk of carbapenem-resistant enterobacteriaceae (CRE) infection and mortality in patients who test positive for carriage of CRE (19,20). To the best of our knowledge, there is no previous study from Greece focusing on both VRE and CRGN rectal carriage, exploring respective risk factors and adverse outcomes.…”
Section: Introductionmentioning
confidence: 75%
“…Little is known, though, about the mechanisms that promote progression from carriage to infection. Increased total LOS among CRE carriers has been previously described (19,49), as well as the association with increased rate of CRE infections and high mortality (19,20). Previous research has demonstrated that CRE infections are associated more often with sepsis and increased early mortality rate (52), particularly in vulnerable patients such as pediatric, geriatric, immunosuppressed, hospitalized, and chronically ill (53,54).…”
Section: Discussionmentioning
confidence: 91%
“…Although several studies have identified CRE colonization as a risk factor for subsequent CRE infection (6,7), available investigations do not explore whether this risk differs based on the production of carbapenemases by the colonizing strain. This information is important because it can guide whether the additional step of performing phenotypic or genotypic testing on rectal isolates positive for CRE provides added value.…”
mentioning
confidence: 99%
“…Gut colonization by CRE is an independent risk factor for CRE infection [7,8,11,12]. An Italian multicenter study showed that in patients who underwent autologous and allogeneic HSCT, the CRE colonization rates were 1 and 2.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%